การจัดการสื่อโปรแกรมประยุกต์เพื่อการเรียนรู้ ประวัติศาสตร์และวัฒนธรรมของพื้นที่กลางเวียงเชียงใหม่ - ชวณัฐ สุวรรณ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The research titled, “Application Management for Historical and Cultural Learning in the Klangwiang Chiang Mai Area”, aimed at studying historical context, physical characteristics of the area, cultural heritage, learning resources in Klangwiang Chiang Mai area, along with conditions and problems on Chiang Mai historical and cultural learning. These were analyzed and presented in the styles and methods of application management in order to increase efficiency in historical and cultural learning around Klangwiang Chiang Mai area. The researcher studied history and values towards various fields of studies on cultural heritage and learning resources in Klangwiang Chiang Mai area. The researcher studied through documents, interviews with arts and cultural specialists, population and tourists in Chiang Mai city. Moreover, conditions and problems of the medium for historical and cultural learning both inside and outside of the places were surveyed. Cultural heritage and learning resources can be classified in 4 groups from the results of the study; temples, ancient remains, museums, and monuments. All groups are valuable for collaborative learning in terms of history, culture, arts, and society. The researcher analyzed problems conditions of learning medium both inside and outside of the places and considered the results together with interview results and opinion from samples. The results were used as a guideline for creating learning processes through suitable application. The researcher studied samples of application for learning world’s important historical cities and application about tourism in Chiang Mai that are available today. Therefore, the researcher knew general usage patterns, along with advantages and disadvantages of those programs in order to use them as basic information to design and manage data of applications. The results from data management consisted of 1) Map: gathering information about places and showing the position of learning resources. 2) Route: preparing routes for visiting learning resources according to their types which are routes to temples, ancient remains, museums, monuments, and mixed types of important places of Klangwiang Chiang Mai area. Therefore, users can choose to study upon their interests and time. 3) More: applications are tools to help enhance efficiency of historical and cultural learning in real places. Furthermore, fewer budgets were used to produce this program than fixing old information signs which can communicate to only few people. In addition, they were left without cares, damaged, and look uninteresting. In conclusion, applications help encourage self-learning through technology which correspond to the present learning situations.